Investments - Bodie, Zvi; Kane, Alex, 1942-; Marcus, Alan J. (New York, NY : McGraw-Hill Education, 2021)
"Investments, Twelfth Edition, is intended primarily as a textbook for courses in investment analysis. Our guiding principle has been to present the material in a framework that is organized by a central core of consistent funda-mental principles. We attempt to strip away unnecessary mathematical and technical detail, and we have concen-trated on providing the intuition that may guide students and practitioners as they confront new ideas and chal-lenges in their professional lives"--
Includes index.
Ages 18+
BBS
Keywords: Investments; Portfolio management